Effects of a Berry Polyphenolic Fraction on the Pathogenic Properties of Porphyromonas gingivalis - Katy Vaillancourt; Amel Ben Lagha; Daniel Grenier (Frontiers Media S.A., 2022)
Porphyromonas gingivalis expresses a broad array of virulence factors that enable it to play a central role in the etiopathogenesis of periodontitis. The objective of the present study was to assess the effects of a berry polyphenolic fraction (Orophenol®) composed of extracts from cranberry, wild blueberry, and strawberry on the main pathogenic determinants of P. gingivalis. Orophenol® attenuated the growth of P. gingivalis and decreased its hemolytic activity, its adherence to a basement membrane matrix model, and its proteinase activities. The berry polyphenolic fraction also impaired the production of reactive oxygen species (ROS) by oral keratinocytes stimulated with P. gingivalis. Lastly, using an in vitro model of oral keratinocyte barrier, the fraction exerted a protective effect against the damages mediated by P. gingivalis. In conclusion, the berry polyphenolic fraction investigated in the present study attenuated several pathogenic properties of P. gingivalis. Although future clinical investigations are required, our study provided evidence that the polyphenols contained in this fraction may represent bioactive molecules of high interest for the prevention and/or treatment of periodontal disease.